2021
DOI: 10.1051/0004-6361/202040162
|View full text |Cite
|
Sign up to set email alerts
|

Properties of stream interaction regions at Earth and Mars during the declining phase of SC 24

Abstract: Aims. We inspect the evolution of stream interaction regions (SIRs) from Earth to Mars, covering the distance range 1–1.5 AU, over the declining phase of solar cycle 24 (2014–2018). So far, studies only analyzed SIRs measured at Earth and Mars at different times. We compare existing catalogs for both heliospheric distances and arrive at a clean dataset for the identical time range. This allows a well-sampled statistical analysis and for the opposition phases of the planets an in-depth analysis of SIRs as they … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 36 publications
(49 reference statements)
2
27
0
Order By: Relevance
“…As the dose rate is varying in time, one can not quantify the reduction by simply calculating the dose rate difference before and during the parking. The modulation of the GCR radiation during this period (in which there were no major solar eruptions) is mainly driven by recurrent CIRs that follow the periodic rotation of the Sun (Geyer et al 2021), we expect that the measured dose rate would have been equal to the dose rate during the same phase of the previous cycles, if no extra butte shielding had been present. To illustrate this idea, we superpose the RAD measurements during each of the first five solar rotation cycles, which are marked from I to V in Fig.…”
Section: Regolith Shielding At Murray Buttesmentioning
confidence: 99%
See 3 more Smart Citations
“…As the dose rate is varying in time, one can not quantify the reduction by simply calculating the dose rate difference before and during the parking. The modulation of the GCR radiation during this period (in which there were no major solar eruptions) is mainly driven by recurrent CIRs that follow the periodic rotation of the Sun (Geyer et al 2021), we expect that the measured dose rate would have been equal to the dose rate during the same phase of the previous cycles, if no extra butte shielding had been present. To illustrate this idea, we superpose the RAD measurements during each of the first five solar rotation cycles, which are marked from I to V in Fig.…”
Section: Regolith Shielding At Murray Buttesmentioning
confidence: 99%
“…SIR properties at Mars Recently, Huang et al (2019) have used the MAVEN measurements during the period from October 2014 to November 2018 and identified 149 SIRs and their associated shocks at Mars. Geyer et al (2021) further analyzed these events comparing in-situ solar wind data at Earth and Mars using as well the remote sensing image of the Solar coronal holes. Comparing the properties of SIRs at Mars to those at Earth, these studies found that (1) most SIRs are well formed at 1 au; (2) the average duration of SIRs at Mars is about 37.0 h, comparable to that at Earth (36.7 h) indicating that there is no significant expansion as they move radially outward up to 1.5 au; (3) the crest of the HSS profile broadens by about 17%, and the magnetic field and total pressure by about 45% around the stream interface; (4) the maximum magnetic field strength and pressure of SIRs decrease significantly from 1 to 1.5 au; (5) occurrence rate of fast forward shocks is about three times as high at Mars than at Earth.…”
Section: Recurrent Forbush Decreases On Marsmentioning
confidence: 99%
See 2 more Smart Citations
“…From real-time monitoring of the ESWF service and post-event analysis, it was recognized that the modeled solar wind speed profile is too gradual as compression and rarefaction effects are not considered by the smooth increase and decrease in the observed evolution of the coronal hole. Superposed epoch analysis has shown that the median time-velocity profile of a CIR consists of a sharp increase followed by longer recovery phase (Geyer et al, 2021). As of yet, this asymmetrical shape is not being considered by the ESWF model.…”
Section: Introductionmentioning
confidence: 99%